APPLICATION OF US-SCS CURVE NUMBER METHOD AND GIS FOR DETERMINING SUITABLE LAND COVER OF SMALL WATERSHED A case study of Pakuwojo Sub-Watershed (Part of Dieng Plateau Area ), Wonosobo Regency, Central Java, Indonesia - , Christanti Nana Widiyati, Prof. Dr. H.A. Sudibyakto, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Pakuwojo Sub-Watershed has experienced rapid changes in its physical condition. Most of forest coverage has changed into agricultural plantation. This result in bad hydrological condition of the area. High amount of surface run-off triggers natural disaster in rainy season. Existing land use is estimated cause high amount of surface run-off. This study aims to reveal the appropriate land cover for the area which can reduce run-off yield. Run-off estimation is conducted using US-SCS Curve Number method. Four land cover scenarios are developed to reveal which one of existings land cover types is appropriate for the study area in term of reducing run-off yield.To make a validation of the application US-SCS Curve Number Method, calculating observational run-off is required. Statistical analysis is than used to test those two run-off data result from two different methods. The result of this study shows that actual run-off depth of the area is 2143,0 mm and peak discharge is 91,76 m3/s. The result also reveals that forest coverage can reduce dramatically surface run-off about 48,38 percent. Potato increases surface run-off 1,59 percent, on the contrary, applying cacica papaya as the main coverage can reduce surface run-off 24,6 percent. Carica papaya is expected as the alternative commodity which can substitute potato as the main commodity. Scenario 4 is developed based on the result of the previous scenario on run-off yield. This scenario consist of five types of land coverage i.e forest, settlement, potato, carica papaya and mix garden. An expansion on forest and carica papaya coverage in this scenario is expected will bring better condition on hydrological regime in the area. In this scenario, local people still can have some areas for vegetable plantation (potato and mix garden) for daily needed or for commercial. Run-off yield result from scenario 4 is 1690,40 mm or decrease 21,14 percent from actual run-off. Statistical analysis reveals that there is no difference between observed run-off depth and estimated run-off dept in the level of significancy 5 %.